2019
DOI: 10.1021/acsami.9b06029
|View full text |Cite
|
Sign up to set email alerts
|

Self-Limited Nanosoldering of Silver Nanowires for High-Performance Flexible Transparent Heaters

Abstract: Silver nanowires (Ag NWs) are key materials to fabricate next-generation flexible transparent electrodes (FTEs). Currently, the applications of Ag NWs are impeded by the large wire−wire contact resistance. Herein, a selflimited nanosoldering method is proposed to reduce the contact resistance by epitaxially depositing silver nanosolders at the Ag NW junctions, which have a negligible effect on the optical transparency, while decreasing the sheet resistance of the Ag NW film from 18.6 to 7.7 Ω/sq at a transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…To make such heaters, engineered nanomaterials such as metal nanowires [17][18][19] , carbon nanotubes 20 , graphene 21 , and other nanocomposites 4,22 have been proposed. In general, the film heaters are of different types such as metal oxide thin film-based heaters 23 , carbon nanostructures-based heaters 9 , metal nanowire network-based heaters 24,25 , metal mesh 26 , and hybrid electrodes-based heaters as reviewed in a work by Gupta et al 4 . Among those, hybrid electrodes-based heaters make use of mesh-like architecture in combination with the conductive films 27 .…”
Section: Introductionmentioning
confidence: 99%
“…To make such heaters, engineered nanomaterials such as metal nanowires [17][18][19] , carbon nanotubes 20 , graphene 21 , and other nanocomposites 4,22 have been proposed. In general, the film heaters are of different types such as metal oxide thin film-based heaters 23 , carbon nanostructures-based heaters 9 , metal nanowire network-based heaters 24,25 , metal mesh 26 , and hybrid electrodes-based heaters as reviewed in a work by Gupta et al 4 . Among those, hybrid electrodes-based heaters make use of mesh-like architecture in combination with the conductive films 27 .…”
Section: Introductionmentioning
confidence: 99%
“…This method can decrease R sh from 18.6 to 7.7 Ω sq −1 while preserving a constant optical transmittance of 90%. [ 169 ] The first demonstration of AgNW networks being efficiently used as THs was published in 2012 by Celle et al [ 42 ] These authors showed that the intrinsic features of AgNW random networks made it possible to combine bendability, transparency and high heating performances at low voltages (below 12 V), which constitutes a clear asset for integration in many applications. [ 42 ] This demonstration, on both glass and polymeric substrates, was followed by numerous publications.…”
Section: The Investigated Materials Technologies For Transparent Heatersmentioning
confidence: 99%
“…With the increasing demands for smart wearables, optoelectronics and temperaturepreservation device, electrical heaters which have light weight, high strength, ultra-flexibility and rapid response have received widespread attentions [1][2][3][4][5] . Electrical heaters which increase temperature by converting electrical energy into thermal energy can meet the requirements for different scenes such as smart clothing, defogging, ice melting and water heating [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%